`Eumaeus': Literally the Antepenultimate Episode - Slote, Samuel (My University, 2022)
Of the various threads woven into the definitions of Modernism, one is the element of style. One can trace this emphasis on style back to Flaubert’s famous claim, from a letter from January 1852, apropos Madame Bovary: “What I’d like to do is write a book about nothing, a book dependent on nothing external, which would be held together by the internal strength of its style [. . .] a book which would have almost no subject, or at least a subject that is nearly invisible.” 1 Flaubert’s hypothesized work is one that is about nothing other than itself, its manner, its craftmanship. In his eloquent survey of the evolution of Modernism’s preoccupation with style, Ben Hutchinson writes: “Time and again the reification of style threatens to reduce modernity to a mere pretext for hermetic, ‘pure’ aestheticism.” 2 Taking this critique of Modernism to a self-promotional extreme was the Brazilian novelist Paulo Coelho, who in 2012 claimed to much international press coverage that Joyce’s emphasis on style was deleterious to literature: “There is nothing there. If you dissect Ulysses, it gives you a tweet. [. . .] I am modern because I make the difficult seem easy, and so I can communicate with the world.”3 Amid the exuberance of style, there is no substance, just a subject that is, at most, almost invisible, with merely 140 or so characters.
PUBLISHED